Graphene-reinforced nanoantenna at mid-infrared frequencies - Zhao, Qian (2019)
With the more and more research and study on graphene, people have a more understanding on the new material. So far, graphene has already been applied for many applications such as censoring, wireless communication, biology devices and so on. This paper is to study the system of graphene-based nanoantenna. Au (gold) as the material of nanoantenna, which on a monolayer of graphene. Because of the SPP (surface plasmon polariton) and LSP (localized surface plasmon) phenomenon between the surface of graphene and gold nanoantenna will enhance the optical and electrical interaction. By tuning the frequency and voltage to achieve the purpose of the graphene electric property changing. COMSOL Multiphysics 5.4 considered as the simulation software for this project. We go through the 2D simulation of graphene first then followed by 3D simulation. Further study is more focus on the frequency and more potential applications / devices will be create once this issue is improved.